Academic Supervision of PAI Teacher Performance in Educational Foundations Walisongo Magelang - Sulaeman Sulaeman; Junedi Junedi; Rokhmad Afif; Wang Joshua; Ling Barra (al-fikrah: Jurnal Manajemen Pendidikan, 2023)
The success of education cannot be separated from the teacher's performance in learning activities. Academic supervision carried out by the principal is one of the supporting activities in improving teacher performance in teaching. The aim of the research is to describe and analyze the academic supervision of PAI teachers in lesson planning, learning implementation, and learning evaluation. The paradigm of this research is post-positivism. The analysis of this research includes the stages before in the field, during the field and after in the field. The results of the study show that the principal has carried out supervision by showing that the teacher's planning and implementation skills in learning are competent, it's just that there are still a few weaknesses in the teacher in carrying out evaluations, the principal must pay more attention to the evaluation aspect of supervision, whereas in terms of  teaching performance, the teacher must be more improve its performance in the aspect of learning evaluation and follow-up of student assessment results. school principals must pay more attention to the evaluation aspect of supervision and teachers must further improve their performance in the evaluation aspect of learning and following up on student assessment results. The recommendation of the researcher  the next that the implementation of academic supervision at the Walisongo Education Foundation in Magelang has quite significant implications for increasing the professionalism of teachers there. If the principal is more intent on implementing academic supervision, the teacher's performance will be more competent